2020
DOI: 10.1111/nph.16374
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for contrasting roles of dimethylsulfoniopropionate production in Emiliania huxleyi and Thalassiosira oceanica

Abstract: Summary Dimethylsulfoniopropionate (DMSP) is a globally abundant marine metabolite and a significant source of organic carbon and sulfur for marine microbial ecosystems with the potential to influence climate regulation. However, the physiological function of DMSP has remained enigmatic for >30 yr. Recent insight suggests that there are different physiological roles for DMSP based on the cellular DMSP concentrations in producers. Differential production of DMSP was tested with multiple physiological experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…Prediction of in situ DMSP production is challenging, and the cellular roles of DMSP in producers remain unknown. However, recent work suggests that the two groups of DMSP producers, HiDPs and LoDPs, regulate DMSP synthesis for different cellular roles (McParland et al ., 2020). Accurate quantification of these two groups, particularly the HiDPs which appear to produce DMSP constitutively, could result in more accurate predictions of in situ DMSP production (Lyon et al ., 2011; McParland and Levine, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prediction of in situ DMSP production is challenging, and the cellular roles of DMSP in producers remain unknown. However, recent work suggests that the two groups of DMSP producers, HiDPs and LoDPs, regulate DMSP synthesis for different cellular roles (McParland et al ., 2020). Accurate quantification of these two groups, particularly the HiDPs which appear to produce DMSP constitutively, could result in more accurate predictions of in situ DMSP production (Lyon et al ., 2011; McParland and Levine, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work based on measurements of DMSP in many different isolates demonstrated that DMSP producers can be divided into two groups: high DMSP producers (HiDPs) and low DMSP producers (LoDPs). The two groups are defined by both the intracellular DMSP concentrations of producers, and changes in DMSP concentrations in response to different environmental conditions (McParland and Levine, 2019;McParland et al, 2020) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted in N. tabacum plants, short-term and low-dose SS induced metabolic shifts toward gluconeogenesis, which involved accumulation of mainly glucose, sucrose and fructose with depletion of pyrimidine and purine metabolites, while a high-dose of salt increased the accumulation of the osmolytes proline, myo-inositol and GABA [ 61 ]. Dimethylsulfoniopropionate (DMSP) is produced by a large diversity of macroalgae [ 110 ] and has a significant impact on SS and temperature shifts [ 111 , 112 ]. Intracellular functions of DMSP are not well understood but this molecule has been proposed to act as an osmoregulator [ 113 ] and antioxidant [ 114 ].…”
Section: Metabolic Reprogramming In Plants Responding To Ssmentioning
confidence: 99%
“…In addition, we measured the photosynthetic efficiency of photosystem II (Fv/Fm) 410 for these two strains when acclimated to 28° C using a PHYTO-PAM with an excitation 411 wavelength set to 645 nm for C-phycocyanin and allophycocyanin (Heinz Walz, Effeltrich, 412 Germany). Fv/Fm measurements were made using triplicate cultures and three technical 413 replicates each that were dark acclimated for 20 minutes, as in McParland et al (2019).…”
Section: Photophysiology Measurements 398mentioning
confidence: 99%